Analyzing the Impact of Fashion Influencer on Online Impulsive Buying Behavior - Prihana Gunawan , Najla; Permadi Iskandar, Ir. Budi (KnE Social Sciences, 2020)
As the internet has growth expeditiously, many people use the internet also for running their business and use one of the most powerful platforms on the internet, which is social media. To market their product, there are several ways to promote the product and to attract the customer such as by endorsing people that interested in fashion and can give influence to their followers, called Fashion Influencer. One of the main reason why people buy a product is because of the recommendation of fashion influencer on social media, people buy for something that they don’t intend to buy it. And the impulse buying behavior happens.This research aims to analyze and identify the impact of fashion influencer marketing on Instagram to customer impulsive buying behavior and related to the fashion style adopted by the online consumer using a diffusion of innovation theory. This research used a qualitative approach with a semi-structured and in-depth interview, and quantitative approach through a questionnaire to validate the data by knowing the percentage of consumer based on the sample was conducted. The result of coding interpretation and questionnaire shows that 80% of participants are adopting the fashion product and influenced by a purely specific influencer that leads to impulsive buying Results indicate that macro influencer affects the impulsive purchase of fashion product to early majority stage and self-updated stage. Micro influencer affects the impulsive purchase of fashion product to early adopter fashion adaptation stage and leads to pure impulsive buying of the consumer. Keywords: fashion influencer, fashion adaptation style, impulsive buying behavior, online shopping, diffusion of innovation